Multimodal Analysis of Estimated and Observed Social Competence in Preschoolers With/Without Behavior Problems - Dias, Talita Pereira; Gil, Maria Stella Coutinho de Alcantara; Del Prette, Zilda Aparecida Pereira (Paidéia (Ribeirão Preto), 2013)
Social skills compete with behavior problems, and the combination of these aspects may cause differences in social competence. This study was aimed at assessing the differences and similarities in the social competence of 26 preschoolers resulting from: (1) groups which they belonged to, being one with social skills and three with behavior problems (internalizing, externalizing and mixed); (2) types of assessment, considering the estimates of mothers and teachers, as well as direct observation in a structured situation; (3) structured situations as demands for five categories of social skills. Children’s performance in each situation was assessed by judges and estimated by mothers and teachers. There was a similarity in the social competence estimated by mothers, teachers and in the performance observed. Only the teachers distinguished the groups (higher social competence in the group with social skills and lower in the internalizing and mixed groups). Assertiveness demands differentiated the groups. The methodological aspects were discussed, as well as the clinical and educational potential of the structured situations to promote social skills.